Development of An Interactive E-Module Based on Green Chemistry on Reaction Rate Matter - Rahmani, Mei; Pulungan, Ahmad Nasir; Ridho, Dimas; Kurniawan, Ekin Dwi Arif (Pendidikan Kimia FKIP Universitas Jambi, 2025)
This study aims to develop an interactive e-module based on green chemistry in the reaction rate material to improve learning outcomes and foster students' interest in learning. The research employed the Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate), which in this study was limited to the Develop stage. The research subjects consisted of 2 lecturers, 1 chemistry teacher, and 32 students from from the Grade XI Science A-1 class at State Islamic Senior High School 1 Medan (MAN 1 Medan), selected through purposive sampling. The research instruments included test instruments (pretest and posttest questions) and non-test instruments (validation questionnaires and student learning interest questionnaires). Based on expert validation, the interactive e-module was declared highly feasible with an overall average score of 82.00%. In the trial phase, the e-module showed an improvement in student learning outcomes with an N-gain score of 0.69, categorized as moderate, and student interest in learning reached 74%, also falling into the moderate category. Keyword: Interactive e-module, green chemistry, reaction rate, learning outcomes, learning interest.